2020
DOI: 10.4103/ijcm.ijcm_479_19
|View full text |Cite
|
Sign up to set email alerts
|

The habitual additional sodium intake among hypertensive patients visiting a tertiary health-care center, Indore, Madhya Pradesh

Abstract: Background: Hypertension prevalence is related to dietary sodium chloride intake. People are consuming much more sodium than is physiologically necessary. The consumption of processed food in urban India has led to a prevalence of 24%–30% of hypertension. The people have a special liking of such type of foods. This study aimed at assessing consumption of sodium among the study subjects to compare habitual additional consumption of sodium among hypertensive and normotensive patients and to find its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Inamdar et al also revealed that there was more habitual additional sodium consumption among 15-25 years age group. 13 Our study found that 17% of the bank employees were at moderate risk for cardio vascular diseases (CVD). While Shivaramakrishna et al revealed 55% of the study subjects had at least two of risk factors regarding coronary heart disease which are hypertension, diabetes, high cholesterol, high triglyceride, smoking, sedentary lifestyle, positive family history and obesity.…”
Section: Discussionmentioning
confidence: 91%
“…Inamdar et al also revealed that there was more habitual additional sodium consumption among 15-25 years age group. 13 Our study found that 17% of the bank employees were at moderate risk for cardio vascular diseases (CVD). While Shivaramakrishna et al revealed 55% of the study subjects had at least two of risk factors regarding coronary heart disease which are hypertension, diabetes, high cholesterol, high triglyceride, smoking, sedentary lifestyle, positive family history and obesity.…”
Section: Discussionmentioning
confidence: 91%